Cross-sectional association between frequency of vigorous physical activity and academic achievement in 214,808 adolescents - Zhang, Xiaohui; Zhang, Danqing; Yang, Xingyi; Chen, Sitong (Frontiers in Sports and Active Living, 2024)
Background This study explores the intricate link between vigorous physical activity and academic achievement in adolescents. By analyzing data from the Health Behaviour in School-aged Children (HBSC) survey, it seeks to understand how engaging in high-intensity physical activities influences academic achievement. Methods A comprehensive cross-sectional analysis was conducted on a vast dataset comprising 214,808 adolescents aged 11, 13, and 15 years. The frequency of vigorous physical activity was determined through self-reports, while academic achievement was assessed based on students’ self-perceptions, reflecting their understanding of teachers’ evaluations of their academic performance. Results Adolescents who reported engaging in vigorous physical activity daily were more likely to report higher academic achievement. This positive correlation was consistent across various demographic groups, including different age cohorts and both genders, indicating a universal benefit of regular vigorous physical activity on perceived academic success. Conclusion The findings of this study underscore the significant role that regular vigorous physical activity plays in the academic lives of adolescents. The correlation between daily vigorous physical activity and enhanced self-reported academic achievement suggests that encouraging high-intensity physical activities in schools could be a key strategy in boosting educational outcomes.